Effect of a heat-treatment on the linear dimensional change of a hard chairside reline resin - Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP] (Elsevier, 2002)
Statement of problem. Little data are available regarding the effect of heat-treatments on the dimensional stability of hard chairside reline resins. Purpose. The objective of this in vitro study was to evaluate whether a heat-treatment improves the dimensional stability of the reline resin Duraliner II and to compare the linear dimensional changes of this material with the heat-polymerized acrylic resin Lucitone 550. Material and methods. The materials were mixed according to the manufacturer's instructions and packed into a stainless steel split mold (50.0 mm diameter and 0.5 mm thickness) with reference points (A, B, C, and D). Duraliner II specimens were polymerized for 12 minutes in water at 37°C and bench cooled to room temperature before being removed from the mold. Twelve specimens were made and divided into 2 groups: group 1 specimens (n=6) were left untreated, and group 2 specimens (n=6) were submitted to a heat-treatment in a water bath at 55°C for 10 minutes and then bench cooled to room temperature. The 6 Lucitone specimens (control group) were polymerized in a water bath for 9 hours at 71°C. The specimens were removed after the mold reached the room temperature. A Nikon optical comparator was used to measure the distances between the reference points (AB and CD) on the stainless steel mold (baseline readings) and on the specimens to the nearest 0.001 mm. Measurements were made after processing and after the specimens had been stored in distilled water at 37°C for 8 different periods of time. Data were subjected to analysis of variance with repeated measures, followed by Tukey's multiple comparison test (P<.05). Results. All specimens exhibited shrinkage after processing (control, -0.41%; group 1, -0.26%; and group 2, -0.51%). Group 1 specimens showed greater shrinkage (-1.23%) than the control (-0.23%) and group 2 (-0.81%) specimens after 60 days of storage in water (P<.05). Conclusion. Within the limitations of this study, a significant improvement of the long-term dimensional stability of the Duraliner II reline resin was observed when the specimens were heat-treated. However, the shrinkage remained considerably higher than the denture base resin Lucitone 550. Copyright © 2002 by The Editorial Council of The Journal of Prosthetic Dentistry.
Keywords: acrylic acid resin; stainless steel; water; duraliner II; Lucitone; methacrylic acid derivative; poly(ethyl methacrylate)n butyl methacrylate; poly(ethyl methacrylate)n-butyl methacrylate; polymer; analysis of variance; cooling; denture; distillation; heat treatment; linear system; polymerization; room temperature; temperature; chemistry; comparative study; confidence interval; heat; human; materials testing; reproducibility; statistics; surface property; time; Acrylic Resins; Analysis of Variance; Confidence Intervals; Denture Bases; Denture Rebasing; Heat; Humans; Materials Testing; Methacrylates; Polymers; Reproducibility of Results; Statistics; Surface Properties; Time Factors; Water